To Dream the Impossible Dream: The Commitment by the Institute for Clinical and Economic Review to Rewrite the Axioms of Fundamental Measurement for Hemophilia A and Bladder Cancer Value Claims - Paul Langley (University of Minnesota Libraries Publishing, 2020)
Understandably, after 30 years of ignoring the axioms of fundamental measurement, advocates of creating approximate information through the construction of lifetime cost-per-QALY worlds are somewhat unnerved by the realization that their methodology is incompatible with those axioms. This is made all the more unnerving when it is pointed out that this incompatibility was pointed out over 30 years ago, following the formalization of those axioms almost 80 years ago. Why this was overlooked is a mystery. The result was a commitment to the application of ordinal utility and other patient reported outcome measures to support claims for response to competing therapies; most egregiously, the advocacy of cost-per-QALY lifetime models and willingness to pay thresholds to support recommendations for pricing and access to pharmaceutical products and devices. Although this incompatibility has been pointed out in respect of simulation modeling, to groups such as the Institute for Clinical and Economic Review (ICER) they press on, producing evidence reports and recommendations for emerging products that fail the standards of normal science.  While these are an analytical dead end, ICER has nowhere else to go. This is their business model; to admit otherwise would mean withdrawing their many evidence reports and admit they were wrong. ICER has rejected this; rather it has decided, together with its academic consultants, to challenge the axioms of fundamental measurement, to produce a parallel measurement universe that can sustain QALYs and the imaginary simulation lifetime models. The purpose here is to make clear that ICER is manifestly wrong and that there is no way it can maintain its credibility in pursuing this path. This is achieved by a deconstruction of the arguments put forward by ICER to defend its new vision of the axioms of fundamental measurement, a vision which provides a case study in the distinction between justified belief and opinion.  Fortunately, we have the framework for a new paradigm in value assessment; a paradigm that recognizes the standards of normal science and rejects belief in an alternative reality consistent with fundamental measurement axioms.